Assessing the Relationship between Supervisors and Employees - Matthew Benge (EDIS)
Relationship-based leadership is characterized by trust, respect, and mutual obligation that generates influence between parties. Within UF/IFAS Extension especially, many relationships between supervisors and employees are dynamic and multidimensional, characterized as both supervisory and collegial. Leader-Member Exchange Theory (LMX) is a relationship-based approach that explains leadership as an interaction between both leader and follower. In this new 4-page publication of the UF/IFAS Department of Agricultural Education and Communication, Matthew Benge presents the LMX-7, an assessment instrument to gauge the quality of relationship between supervisors and their employees. http://edis.ifas.ufl.edu/wc332